Adaptive boundary element method and error analysis - Wang, Xin. (2010)
The adaptive boundary element method is a process for which computer can be used to justify and improve the accuracy of boundary element solutions automatically. Although adaptive processes are very important to ensure the effectiveness and correctness of a numerical analysis, there are many arguments with the current schemes used in adaptive boundary element analysis. This thesis aimed to improve those schemes and develop a more effective adaptive computer program.